Revisiting the Dusunic boat lutes of Sabah: disappearing musical traditions - Jacqueline Pugh-Kitingan (UPSI Press, 2020)
The Kadazan Dusun sundatang from Tambunan, the Rungus sundatang, and the Lotud gagayan are three kinds of boat lutes from Sabah. Each is carved from a single log of jackfruit wood, but they vary structurally. Resembling somewhat Philippine boat lutes, they differ from the sape-types of Sarawak and Kalimantan. They are played solo in non-ritual contexts. The gagayan, however, was played in pairs and the Tambunan sundatang was sometimes accompanied by a hand-held gong when accompanying the slow, sedate magarang sundatang dance. Today, there are very few musicians playing the unique Tambunan sundatang, while the Lotud gagayan has recently declined with the demise of older performers. The Rungus sundatang is still extant and continues to be performed in many longhouses. This paper discusses these three types of Dusunic boat lutes, their structures, performance practices and music, and suggests a possible origin for these kinds of instruments found in northern Borneo.